Evaluasi Pertumbuhan dan Seleksi Tanaman Padi Aksesi BC2F2 Toleran Cekaman Terendam Serta Persilangan balik-nya dengan Tetua Lokal - Meri Hasmeda; Entis S. Halimi; Rizky Yudhan Guswari (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Hasmeda et al, 2017. Growth Evaluation and Selection of Several BC2F2  Rice Accession Tolerant to Submergence Stress and Their Backcrossing to Local Parent. JLSO 6(1):7-20. This study was aimed to conduct selection process upon the four accessions of BC2F2 rice which were tolerant to submerging stress during vegetative stage. The selected plants were crossed with local parents. Local parents being used in this experiment consisted of Payak Silembuk, Siam, Pegagan, and Pelita Rampak.  There were several backcrossing being observed i.e. BC2F2 Accesion (BC2F2Py.Silembuk, BC2F2.Siam, BC2F2.Pegagan, and BC2F2P.Rampak) which were evaluated on the 20th day after being planted for 14 days. Parameters were observed before and after submerging process. The data obtained were analyzed with the Least Significant Difference (LSD) formula. As the result, BC2F2Pys accession had better tolerance compared with the rest of accessions and showed consistent resultsas the previous research. It is concluded that the accession of BC2F2Py.Silembuk showed the best performance among the other  of BC2F2.